ANALISIS DAN PREDIKSI KETERGANGGUAN KEGIATAN BELAJAR MENGAJAR AKIBAT KEBISINGAN YANG DITIMBULKAN DARI KEGIATAN DI CAMPUS CENTER ITB - ADYARINI S, IRMA
Noise is an unwanted sound. Annoyance is one of noise’s impacts. The objectives of this research are to analyze and to predict annoyance level in the classroom due to noise activities at Campus Center ITB. The main sources of noise are student activities beyond academic schedules such as activities in canteen, organizations and amphitheatre. This noise is classified as a sound which takes places in public spaces with specific level and frequency. The noise that will be produced by the future activities in the student center is obtained from literature and analogical comparison of similar activities in campus. The range of noise for the highest activities at Campus Center in outdoor is predicted between 63.2 – 68.3 dBA. It’s not suitable with the standards set by KepMen LH no.48 1996 for school noise area. The noise level inside researched classroom, 9008, 9009 and planologi, will be obtained by considering the distance between the noise source and receiver location of the existing noise condition as well as the noise reduction of the partition. The result is between 40.8-54.1 dBA . After comparing with the EPA criteria, March 1974 for indoor activities, the noise level inside 9009, Planologi 1st floor and Planologi 5th floor are not suitable with the criteria, but 9008 and Planologi 3rd floor are suitable. The General Annoyance Curve for ITB Students will be obtained from noise simulation at laboratory by using the object questionnaire to ITB students that judge an annoyance range of 0 -10 for 3 noise levels. This curve will be used to predict the actual annoyance level experienced by students in the classroom, that is between 2.9- 4.3 and it includes slight annoyance and slight-medium category.